(untitled) (Journal of Hama University, 2021)
This study aimed to know the impact of innovation in banking products on the competitive advantage of banks operating in the Lattakia Governorate from the customers’ point of view, and in order to achieve this, the researcher selected a random sample that included 100 clients from the study population represented by clients of public and private banks in Lattakia Governorate. The questionnaire was distributed to them and its validity and reliability were verified as it included 20 items, and the data were entered into the computer and processed using the SPSS statistical program, and the study reached the following results:  There is a statistically significant relationship between innovation in banking products and the competitive advantage of banks operating in Lattakia Governorate.  The existence of a statistically significant relationship between (originality, and the tendency to highlight details) as two dimensions of innovation in banking products and the competitive advantage of banks operating in Lattakia Governorate.  The absence of a statistically significant relationship between (fluency, flexibility, ability to sense problems) such as dimensions of innovation in banking products and the competitive advantage of banks operating in Lattakia Governorate.